'By the Will of the Pike': The transformation of a Russian national character. Issue 2 (1st November 2017) - Nikolajeva, Maria
This article explores some versions and film adaptations of the Russian folk tale about lazy Yemelya and the wish-granting pike. It argues that the folk tale reflects fundamental traits of Russian mentality and demonstrates how the versions transform the main character according to the prevalent ideology of their particular socio-historical context. For instance, the film adaptations created during the Soviet regime replace the lazy, simple-minded and self-conceited protagonist of the folk tale with a kind and brave representative of the 'ordinary people' oppressed by the king. In various paratexts he is invariably characterized as 'kind and brave'. Moreover, he is portrayed as hard-working, clever and good-looking, which makes the pike's gift a reward for existing virtue rather than an unexpected piece of luck, emphasizing class conflict and solidarity with the poor. A closer look at the film versions confirms Jack Zipes's claim that folk tales are frequently employed for ideological purposes.